2014
DOI: 10.15406/jlprr.2014.01.00011
|View full text |Cite
|
Sign up to set email alerts
|

Smell, Lung Cancer, Electronic Nose and Trained Dogs

Abstract: Lung cancer (LC) represents a problem of high magnitude for the medical systems due to its morbidity and mortality, also because of the huge human and economical efforts and costs that it catalyzes. Only in Europe, the average life-time cost of lung cancer patients ranges between €46,000 and €61,000 per patient.Secondary prevention, which consists in mass-screening of the high-risk population, could result of high benefit. For this aim to become a reality in the future, a potentially inexpensive and non-invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Therefore, it could be very useful in the diagnosis and prognosis of lung cancer [ 11 ]. There are several methods that can be applied to analyze the EBC for the identification of volatile compounds emitted by tumor growth, including spectrographic techniques, e-nose and trained dogs [ 12 ]. Thus, Philip et al found a specific alteration of some volatile organic compounds (VOCs) present in EBC that could be considered as a screen for lung cancer in adult smokers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it could be very useful in the diagnosis and prognosis of lung cancer [ 11 ]. There are several methods that can be applied to analyze the EBC for the identification of volatile compounds emitted by tumor growth, including spectrographic techniques, e-nose and trained dogs [ 12 ]. Thus, Philip et al found a specific alteration of some volatile organic compounds (VOCs) present in EBC that could be considered as a screen for lung cancer in adult smokers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%